2002 IEEE International Symposium on Circuits and Systems. Proceedings (Cat. No.02CH37353)
DOI: 10.1109/iscas.2002.1010395
|View full text |Cite
|
Sign up to set email alerts
|

Low power register file architecture for application specific DSPs

Abstract: In this paper, an architecture for register files suited for synthesizable DSP cores is proposed. The principal focus is on the implementation of DSP algorithms with several identical channels, used in e.g. stereo audio, filterbanks or network IC implementations.Nevertheless, it is shown that the result of this work can be extended to many single channel applications by formal assignment of operations to several channels.The new register file architecture is especially suited for a standard semi-custom design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Various studies have shown that register files are major consumers of energy in modern processors [1][2][3]. Different architectures and techniques have been proposed in the literature [4][5][6][7][8][9] where the primary objective was to optimize the energy consumption of register files. Hence, there exists a justifiable need for the accurate power modeling of these components taking into consideration the current nanometer processing technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that register files are major consumers of energy in modern processors [1][2][3]. Different architectures and techniques have been proposed in the literature [4][5][6][7][8][9] where the primary objective was to optimize the energy consumption of register files. Hence, there exists a justifiable need for the accurate power modeling of these components taking into consideration the current nanometer processing technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever Filter 2 is executed, the registers of Filter 1 (Dark area in registerfile of Figure 3) should remain ideally unchanged and viceversa. But due to the single registerfile and a common data bus the registers share, any change in the contents of the data bus would cause spurious transitions on the input of all the registers in the register file [7]. These additional transitions results in increased power dissipation.…”
Section: Power Saving Estimationmentioning
confidence: 99%